Effects of Detached Seaweeds on Structure and Function of Arctic Intertidal Soft-Bottom Communities - Díaz, María José; Buschbaum, Christian; Renaud, Paul E.; Molis, Markus (Frontiers in Marine Science, 2021)
Expected lower sea-ice cover and increased storm frequency have led to projections of an increase in seaweed detritus in Arctic marine systems in the near future. To assess whether detached seaweed affects structural and functional traits of species assemblages in soft-bottom habitats, comparable experiments were run in two intertidal sites (Longyearbyen and Thiisbukta) on Svalbard. At each site, we fixed nets containing the locally dominating seaweeds Saccharina latissima and Desmarestia aculeata (Thiisbukta) or Fucus sp. (Longyearbyen) to intertidal mud flats. Empty nets were fixed as procedural controls at both sites. After 2.5 months, one sediment core was taken from each manipulated plot and the number of individuals, dry mass, and average length of each encountered animal taxon were recorded. The same measurements were taken from cores collected from unmanipulated areas at each site, both at the start and end of the experiment. Abundance data were used to calculate estimates of diversity (Shannon-index, evenness, and taxon richness), while initial and final average length measurements were used to estimate taxon-specific growth. Log response ratios of initial and final abundance in unmanipulated areas were used to estimate magnitude and direction of the effect of change in community traits over time, serving as a reference to log response ratios estimating manipulated seaweed effects. In Longyearbyen, the presence of detached seaweeds reduced abundance and dry mass by, on average, 46 and 70%, respectively, compared to unmanipulated benthic communities. In Thiisbukta, the presence of seaweeds enhanced evenness, on average by 16%, but reduced abundance and growth of benthic fauna by, on average, 31 and 86%, respectively. Seaweed effects were generally smaller in Thiisbukta than in Longyearbyen. At both sites, time effects were generally opposite in direction to those caused by the seaweed treatments, yet of similar or larger magnitude. Through reversing temporal dynamics of several of the tested community traits, detached seaweeds strongly modified the structure and functioning of soft-bottom species assemblages at both intertidal sites. We suggest that the detected effects possibly result from seaweed-induced changes in environmental conditions and/or physical disturbance as underlying processes.